Probing reactivity and substrate specificity of both subunits of the dimeric Mycobacterium tuberculosis FabH using alkyl-CoA disulfide inhibitors and acyl-CoA substrates - Sachdeva, Sarbjot (2007)
The dimeric Mycobacterium tuberculosis FabH (mtFabH) catalyses a Claisen-type condensation between an acyl-CoA and malonyl-Acyl Carrier Protein (ACP) to initiate the Type II fatty acid synthase cycle. To analyze the initial covalent acylation of mtFabH with acyl-CoA, we challenged it with mixture of C(6)–C(20) -CoAs and the ESI-MS analysis showed reaction at both subunits and a strict specificity for C(12)-CoA. Crystallographic and ESI-MS studies of mtFabH with decyl-CoA disulfide inhibitor revealed decyl chain bound in acyl-binding channels of both subunits through disulfide linkage to the active site cysteine. These data provide the first unequivocal evidence that both subunits of mtFabH can react with substrates or inhibitor. The discrepancy between the observed C(12)-CoA substrate specificity in the initial acylation step and the higher catalytic efficiency of mtFabH for C(18)–C(20) -CoA substrates in the overall mtFabH catalyzed reaction suggests a role for M. tuberculosis ACP as a specificity determinant in this reaction.